Bibliometric analysis of islamic education learning loss in the COVID-19 pandemic - Elihami, Elihami (Linguistics and Culture Review, 2021)
This study seeks to objectively examine Islamic education and learning loss on COVID-19 in South Sulawesi and West Sulawesi. Apart from historical developments, the study attempts to survey the detailed, overt and covert planned manipulations of this practice for paranoid purposes. Furthermore, it investigates the inhumane treatment meted out to them as a result of the dreaded coronavirus pandemic, colloquially known as the research community for describing learning loss. The descriptive qualitative approach was used in this study, with data collection techniques such as documentation and data analysis techniques such as data collection, data display, data reduction, data analysis, and data conclusion. In the globalization era, Islamic education faces three challenges: cultural globalization challenges, low levels of social capital challenges, and structural, cultural, and human resource challenges. Meanwhile, the contribution of Islamic education in South Sulawesi can be divided into two major categories: character building contribution in the form of forming good man character, and scholastic contribution. Stakeholders have actually taken advantage of these opportunities. As a result, Islamic education not only exists, but it also contributes significantly to the advancement of education in South Sulawesi.